Kontribusi Strategi Promosi Media Sosial Instagram KAI dan Minat Pengguna Kereta Cepat: Studi Netnografi: The Contribution of KAI’s Instagram Social Media Promotion Strategy to High-Speed Rail Users’ Interest: A Netnographic Study - Murti Pagar Intan; Septia Risma Putri; Muhammad Fatoni; Ovalia Rukmana (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
This study aims to analyze the contribution of PT Kereta Api Indonesia's (KAI) social media promotion program strategy to public interest in using the Whoosh high-speed rail service. The research employs a qualitative approach using netnography. Data were obtained from customer responses on social media by analyzing conversations, comments, and user interactions across platforms to understand public perceptions, preferences, and responses to promotional campaigns associated with relevant hashtags (#PromoKAI, #KeretaCepat, #Whoosh). The data were analyzed using NVivo software to identify themes and patterns in netizen responses. The findings indicate that KAI's promotional programs have been successful in creating awareness and generating initial public interest, particularly through discount offers, giveaways, and engaging visual content. On the other hand, the study also reveals that complaints regarding the clarity of scheduling information, price comparisons with different modes of transportation, and the complexity of the ticket booking process often constrain this interest. This study provides strategic implications for KAI in refining its promotional strategies and digital communication. Theoretically, it enriches the application of netnography in transportation service marketing in Indonesia.